2015
DOI: 10.2466/01.it.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Assignments and Their Impact on Final Examination Grades: An Online Research Methods/Statistics Course

Abstract: Ammons Scientifi c www.AmmonsScientifi c.com CITATION Stack, S. J. (2015) Laboratory assignments and their impact on fi nal examination grades: an online research methods/ statistics course. Innovative Teaching, 4, 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Allain and Williams (2006) found that homework accuracy had no significant impact on test scores in an introductory college astronomy course, but homework completions were not studied. Similarly, Stack (2015) found that exam performance was not statistically related to homework accuracy in an undergraduate research methods/statistics course, but homework completions were not considered. Caudill and Long (2009) found a significantly positive impact of homework accuracy on exam performance, but did not separately consider the effect of homework completions.…”
Section: Homework Assignmentsmentioning
confidence: 99%
“…Allain and Williams (2006) found that homework accuracy had no significant impact on test scores in an introductory college astronomy course, but homework completions were not studied. Similarly, Stack (2015) found that exam performance was not statistically related to homework accuracy in an undergraduate research methods/statistics course, but homework completions were not considered. Caudill and Long (2009) found a significantly positive impact of homework accuracy on exam performance, but did not separately consider the effect of homework completions.…”
Section: Homework Assignmentsmentioning
confidence: 99%